Business Feasibility Study: Consulting Services and Legal Assistance (Case Study on Bilik Hukum) - Agus Angling Kusumah; Frischa Sonawaty Theresia Sianturi; Rhian Indradewa; Semerdanta Pusaka; Agus Munandar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to determine the feasibility of the legal advisory and legal assistance service "Bilik Hukum" from both the financial and business risk aspects. The business finance strategy method focuses on calculating investment value by calculating Return on Investment (ROI), Net Present Value (NPV), Internal Rate of Return (IRR), Average Rate of Return (ARR), Profitability Index (PI), and Payback period (PP). The method in risk management is carried out in six stages, namely (1) risk analysis, (2) risk evaluation. (3) risk management. (4) communication and consultation, (5) monitoring and review, (6) recording and reporting. The results showed that the Bilik Hukum was financially feasible with a positive ROI value from the second to the fifth year, the NPV value was positive at Rp. 10,171,215,666,-, IRR is 68% above the discount rate of 10%, ARR is 319% (greater than 100%), PI is 3.41, and the payback period is 1 year 7 months. Risk management what was done by the Bilik Hukum succeeded in reducing the level of risk impact which was originally at a high level to a medium level and from a medium level to a low level.